2001
DOI: 10.1079/phn2001235
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast consumption in Spanish children and young people

Abstract: Low birthweight is now known to be associated with increased rates of coronary heart disease and the related disorders stroke, hypertension and non-insulin dependent diabetes. These associations have been extensively replicated in studies in different countries and are not the result of confounding variables. They extend across the normal range of birthweight and depend on lower birthweights in relation to the duration of gestation rather than the effects of premature birth. The associations are thought to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
62
1
8

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 44 publications
(81 reference statements)
12
62
1
8
Order By: Relevance
“…Additionally, half of the adolescents consumed products from no more than two of the target food groups together during both the recall days. Similar results were reported in a Dutch study (10) and in Spanish children and adolescents (12) . Sex differences in breakfast consumption have been reported in other studies (1,13) ; however, we found no differences between boys and girls in either frequency of breakfast consumption or breakfast quality.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, half of the adolescents consumed products from no more than two of the target food groups together during both the recall days. Similar results were reported in a Dutch study (10) and in Spanish children and adolescents (12) . Sex differences in breakfast consumption have been reported in other studies (1,13) ; however, we found no differences between boys and girls in either frequency of breakfast consumption or breakfast quality.…”
Section: Discussionsupporting
confidence: 90%
“…Several authors emphasise the importance of breakfast and that it should be included in educational programmes promoting healthy diets and lifestyles 37 or even included in school-based nutrition education programmes, involving families, teachers and others in achieving healthier patterns 7 . In the UK, the Department of Health initiated breakfast club schemes in schools.…”
Section: Discussionmentioning
confidence: 99%
“…Breakfast provides an ideal opportunity for adolescents to begin the day by eating bread, other cereals and fruit, which are all important elements of a healthy and balanced diet. The importance of breakfast consumption in relation to nutritional balance has been shown in different sub-populations 7,9,10 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A good breakfast can contribute to a healthy diet rich in carbohydrates and micronutrients. 45,46 In fact, having an adequate breakfast has been related to both physical and cognitive function and better performance at school in children and adolescents. The breakfast habits have changed in the course of time and the number of breakfast skippers has increased during the last 30 y.…”
Section: Dietary Intake and Food Habits La Moreno Et Almentioning
confidence: 99%